Prunus mume clones as rootstocks for 'Aurora-1' peach in São Paulo State, Brazil and planting density - Mayer, N. A.; Reighard, G. L.; Pereira, F. Mendes [UNESP] (International Society for Horticultural Science (ISHS), 2014)
Dwarf rootstocks allow high density in peach (Prunus persica) orchards and increase productivity. Since 1998, a research project has being carried out at the Faculdade de Ciências Agrárias e Veterinárias (FCAV/UNESP), Jaboticabal Campus, Brazil, involving clones of Prunus mume as rootstocks for peach. In this research, two genotypes ('Clone 15' and 'Rigitano'), propagated by herbaceous cuttings, were tested as rootstocks for 'Aurora-1' peach in three in-row spacings: 6 m x 2 m, 6 m x 3 m and 6 m x 4 m. The experiment was carried out under field conditions in Vista Alegre do Alto (21°10'14S, 48°37'45W, 700 m of altitude), São Paulo State, Brazil. The region has an average accumulation of temperatures ≤ 7.0°C of 17.9 h per year. Evaluations were taken in 2005 and 2006 (2nd and 3rd year after planting, respectively). There were no differences between the two rootstocks on fruit quality, yield and productivity, and no incompatibility symptoms were found on both scion/rootstock combinations. 'Rigitano' and 'Clone 15' are recommended as rootstocks for 'Aurora-1' peach, and the 6 m x 2 m spacing produced the highest fruit diameter and productivity per ha for 'Aurora-1'.
Keywords: Fruiting; Low chill requirement; Physical fruit characteristics; Productivity; Prunus persica